Unveiling the patient-centered approach: exploring the needs of Javanese stroke patients in home health services - Chayati, Nur; Mikami, Akichika; Setyopranoto, Ismail; Effendy, Christantie (International Journal of Public Health Science (IJPHS), 2024)
Home-based care can be effective, efficient, safe, and affordable, if this care is performed using a patient-centered approach. Patient-centered care prioritizes the patient’s needs and preferences. The issue of patient-centered care remains the focus of various parties. This study aimed to explore the expectations of patients who have experienced a stroke, their family caregivers as recipients of home-based care services and healthcare workers as home-based care providers. This study used a qualitative explorative model. Semi-structured interviews were conducted with 19 participants, in addition to 4 focus group discussions. Data was analyzed using a content analysis approach with open code 13 software and the results were presented in COREQ systematics for qualitative studies. There were four main themes present in the results: physical well-being, self-actualization, psychological condition and balance between family burden and coping. Physical limitations were highlighted as the most burden some for the majority of the participants. At the time of the study, the majority of the patients, their family and health workers were diligently working towards to achieving the best outcome regarding physical well-being. Physical well-being is a fundamental need. Reaching this goal, could lead to better self-actualization, better physiological condition and improving the burden on families. This study may be useful as preliminary data to compile a home-based care construct indicators for stroke patients.